(untitled) (Research, Society and Development, 2020)
This article presents an epidemic-behavior model for the SARS-CoV-2 spreading in Amapá employing a generalization of the SIR model, which captures the behavioral response of the population during the epidemic evolution through a reduction factor δ in the contagion rate. The results of the model’s validation step with empirical data show that δ = [0.614,0.638] indicating that the behavioral response was responsible for a reduction of [36,39]% in the epidemic transmissibility. Subsequently, we provide an analysis of the scenarios that may emerge if the isolation measures are lifted tR days after the first peak considering a new reduction factor δR > δ. The results indicate that the careful exit (δR ≤ 0.80) from the confinement measures with 3 weeks (tR = 21) after the first peak can still trigger a second peak, but with a smaller size than the first one.